If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3(1) = -22 Multiply -3 * 1 2x + -3 = -22 Reorder the terms: -3 + 2x = -22 Solving -3 + 2x = -22 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 2x = -22 + 3 Combine like terms: -3 + 3 = 0 0 + 2x = -22 + 3 2x = -22 + 3 Combine like terms: -22 + 3 = -19 2x = -19 Divide each side by '2'. x = -9.5 Simplifying x = -9.5
| 34-(2x+2)= | | x-5(0)=10 | | 3-7x=9+14x | | 4(2+3)+2+-1= | | C/6-7/5 | | -2-5(0)=10 | | 2-6x=5+5x | | 1500=1705x-32015 | | 2(-2.4+0.4y)-3y=-7 | | 6-4x=20+2x | | 4(2-(-3))+2+-1= | | 5*sqrtx^17= | | 5(2x-10)+14/2 | | x(0)-5y=10 | | 5sqrtx^17= | | 3x^2=1+2x | | 4z^2-7=-6z | | 3/4(16-4x)-7=3x+3(x-5)-(x-2) | | 9x-4y=-22 | | 13=-13y+5y | | =x^2+9+20 | | -3(x-4)=6(x-2) | | 0.6x-0.2(12-2x)=-0.4(x-8) | | 7c-3+8+5c= | | 2(-0.7)-3(1)= | | =x^2-9x-70 | | 6x^2+7x+11=0 | | -13y+5y=13 | | 9x-4(4)=-22 | | 2+y/4=3y/8-4 | | 5x^2(3x-2)= | | 9(-3.5+1.5y)-4y=-22 |